Mid-cretaceous rapid denudation of Eastern Tibetan plateau: Insights from detrital records at the Southwestern corner of Sichuan basin - Wang, Zijian; Li, Zhiwu; Ran, Bo; Liu, Shugen; Wu, Wenhui; Ye, Yuehao; Tong, Kui; Hua, Tian; Li, Jinxi (Frontiers in Earth Science, 2023)
Reconstruction of Cretaceous tectonic evolution of the eastern margin of the Tibetan Plateau is of great significance to understanding the formation and early evolution of the Tibetan Plateau. The thick late Mesozoic sedimentary sequence in the Western Sichuan Basin may record the evolution of the basin itself and tectonic uplift history of the eastern margin of the Tibetan Plateau during Cretaceous period. Here we provide new multi-proxy provenance data from conglomerate clast populations, sandstone petrography, heavy mineral assemblages, U-Pb dating of detrital zircon, paleocurrent data, and detrital garnet geochemistry from the Cretaceous clastic units in the southwest corner of Sichuan Basin. Our analysis reveals two distinct changes in sediment provenance recorded in the Cretaceous strata at the southwest corner of the Sichuan Basin. The first significant change of detrital provenance was identifed in the mid-Cretaceous Jiaguan Formation. Metamorphic rocks and volcanic rocks clast as well as feldspar and mica increased significantly, a heavy mineral assemblage dominated by hematite–limonite and ilmenite with high ATi and RuZi and low ZTR values, predominantly type Bi garnet and mostly 164, 207, 440, 780-824 and 1840 Ma detrital zircon ages, interpreted to be sourced from the Songpan-Ganzi fold belt and Longmenshan orogenic belt. The second shift, in the Guankou Formation, is marked by a low compositional maturity, a distinct increase in fossiliferous carbonate clasts and high GZi index with type Bii garnet, and Triassic zircon ages, indicating the exhumation of Longmenshan orogenic belt during the late Cretaceous. These data collectively indicate that the significant surface uplift and rapid denudation of the eastern margin of the Tibetan Plateau were probably initiated in the mid-Cretaceous (~120 Ma). In conclusion, a detailed hands-on provenance analysis of the clastic sedimentary sequences in the southwest corner of Sichuan Basin enabled us to determine catchment areas and shifts hitherto unstudied, thus contributing to the exhumation history of the eastern margin of the Tibetan Plateau.